Ensino de língua inglesa por meio da metodologia webquest: um estudo com alunos do Ensino Médio do IFMA/ Campus São Luís-Monte Castelo - PEREIRA, Cláudia Cristina Cólins (2020)
This research deals with the teaching of the English Language (EL) through the use of active methodologies and contemporary communicative approaches to teaching and learning aimed at teaching the EL. The main objective was to investigate the acquisition of the EL arising from the results of applying the WebQuest Methodology (WQM) associated with contemporary communicative approaches to teaching and learning, such as the Communicative Approach (CA) and the Task-Based Learning (TBL), and from these results, prepare a Pedagogical Guidance Book for English as a Foreign Language (EFL) teachers. In this study, the acronym ABT (Aprendizagem Baseada em Tarefas in the Portuguese language) was identified by the English acronym TBL. The TBL was used in an adapted way for students beginning in the teaching of the EL, and also according to the propositions of Jane Willis. The research was carried out in a class of the first year of technical education integrated to high school from IFMA / Campus São Luís - Monte Castelo. The research participants were twenty-five first-year students and the teacher of the class at that public school. The main theoretical contributions were the works of Dodge (1995; 1997; 2001; 2002), Willis (1996), Nunan (1998), Brown (2001), Harmer (2007), and also the contributions of Leffa (1999; 2016), Almeida Filho (2001; 2007; 2011), Paiva (2001; 2015; 2016), André (2005), Moita Lopes (2006), Bottentuit Júnior (2009; 2010; 2012), Aranha (2015), and official documents including: LDB (BRASIL, 1996), PCN (BRASIL, 1998) and BNCC (BRASIL, 2019). This research was methodologically guided in the qualitative approach, with a method procedure aimed at the instrumental case study approach. In the initial phase of the research, it was used data collection instruments, such as non-participant and participant observations, mixed questionnaire with students, and semi-structured interview with the teacher; in the final phase, interviews were carried out by the Focus Group with the students, and also a final interview with the teacher. For data analysis and interpretation, it was used the students' responses obtained through the questionnaire, and the interviews conducted with the teacher. After the theoretical and methodological procedures developed in this study, we elaborated the product research, which was a Pedagogical Guidance Book, entitled - A linguistic adventure on the Web!. As a final result of the research, we verified that the students, despite the linguistic difficulties, were able to answer the questions asked in the EL, were integrated with the execution of the proposed tasks, and also researched the available links on the WebQuest, presenting good results, both oral and written ones, besides of the product of the WebQuest, which was a bilingual folder, they produced from the applied approaches. With regard to the class teacher, we observed that she expressed an interest in following the conduct of her teaching practice with the integration of other active teaching methodologies, including the WQM in EL.